Nursing students: knowledge of care to people with skin injury - Roberta Kaliny de Souza Costa, Isabelle Campos de Azevedo, Gilson de Vasconcelos Torres, Maria Antônia Teixeira da Costa, Marina de Góes Salvetti (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v5i1.5016